2017
DOI: 10.1167/iovs.17-22452
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Torsion According to Trochlear Nerve Absence in Unilateral Superior Oblique Palsy

Abstract: Citation: Lee JE, Yang HK, Kim JH, Hwang J-M. Ocular torsion according to trochlear nerve absence in unilateral superior oblique palsy. Invest Ophthalmol Vis Sci. 2017;58:5526-5531. DOI:10.1167/iovs.17-22452 PURPOSE. To investigate the relationship between objective ocular torsion and the presence or absence of the trochlear nerve in subjects with unilateral superior oblique palsy (SOP). METHODS.A total of 159 subjects with congenital and acquired unilateral SOP were reviewed. Eighty-four subjects who had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…It should be noted that the excyclotorsion of the non-paretic eye was larger in the present group than in the absent group. Lee et al previously observed that the “net” incyclotorsion in the paretic eye was more frequent in the absent group than in the present group, suggesting that excyclotorsion in the non-paretic eye was more pronounced in the present group [ 7 ]. In this study, we also found a larger excyclotorsion of the non-paretic eye in the present group.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It should be noted that the excyclotorsion of the non-paretic eye was larger in the present group than in the absent group. Lee et al previously observed that the “net” incyclotorsion in the paretic eye was more frequent in the absent group than in the present group, suggesting that excyclotorsion in the non-paretic eye was more pronounced in the present group [ 7 ]. In this study, we also found a larger excyclotorsion of the non-paretic eye in the present group.…”
Section: Discussionmentioning
confidence: 84%
“…Accordingly, the absence of the trochlear nerve and superior oblique muscle (SO) hypoplasia, which can be classified as a congenital cranial dysinnervation disorder, has been accepted as one of the pathophysiologies of unilateral congenital superior oblique palsy (UCSOP) [2][3][4]. Several studies have reported clinical characteristics according to the absence of the trochlear nerve, and Lee et al revealed that the absence of trochlear nerve can contribute to the amount of ocular torsion in unilateral SOP [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is the result of a monocular sensorial adaptation to the cyclodeviation by means of a reordering of the spatial response of retinal elements along new horizontal and vertical meridians [ 20 ]. There is inconsistency and paradoxical measurement when the non-paretic eye or both eyes are measured for extorsion, and sometimes no extorsion is measured despite superior oblique palsy [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in adults, acquired strabismus causing diplopia is the presenting symptom of new paralytic strabismus. For example, superior oblique palsy with a torsional effect that causes diplopia is commonly reported or diagnosed due to signs such as head tilt [ 21 ]. The visual cortex must calibrate the torsion to enable stable vertical orientation under conditions of alternating monocular fixation.…”
Section: Discussionmentioning
confidence: 99%